2019
DOI: 10.5539/ijbm.v14n9p15
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Implementation of International Public Sector Accounting Standards in Pakistan

Abstract: The significance and impact of Accrual-based Public Sector Accounting Standards (APSAS) in financial reporting has in recent times gained traction and has prompted debates which are aligned towards APSAS reporting. This implies that reforms in the government’s management systems are becoming critical towards examination of actions and steps taken to enhance demands for better transparency and accountability in the management of public finance. As is presently presented in Pakistan, there are numerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is also revealed that a well-performing internal audit function will support the financial reporting process and its output quality (Alzeban, 2019). Miraj & Wang (2019) find that the difficulty of accrual-based accounting implementation is related to the lack of monitoring from internal audit function. Higher capability will help overcome this issue.…”
Section: Internal Audit Function Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also revealed that a well-performing internal audit function will support the financial reporting process and its output quality (Alzeban, 2019). Miraj & Wang (2019) find that the difficulty of accrual-based accounting implementation is related to the lack of monitoring from internal audit function. Higher capability will help overcome this issue.…”
Section: Internal Audit Function Capabilitymentioning
confidence: 99%
“…This research provides several significances to fill the gap in the literature. We examine all local governments in Indonesia in order to answer the issue of limited local government observations in previous studies (Gamayuni, 2018;Miraj & Wang, 2019;Muda et al, 2018;Pamungkas, 2018;Suparman, Siti-Nabiha, & Phua, 2015). High coverage will provide a higher generalization ability of the research.…”
Section: Introductionmentioning
confidence: 99%
“…Resources generated from domestic borrowing were used in those projects that contributed to economic growth. Miraj and Wang (2019) highlighted those reforms in government management systems are becoming increasingly important in examining actions and efforts done to improve demands for greater openness and accountability in public finance management. Shaikh and Ali (2020) explored that when developing countries face disasters like COVID 19, the weak budget base and lack of elasticity of budget spending create catastrophic situations, and lack of funds is the biggest problem in such a crisis.…”
Section: Literature Reviewmentioning
confidence: 99%